THE HISTORICAL TRAILS AND INSPIRATION OF RADEN MAS SAID IN GIRILAYU KARANGANYAR ON THE VARIETY OF MBOK SEMOK BATIK MOTIFS - Maslamah; Moh. Fajar Shodiq (2025)
Religious moderation is an important principle in building a harmonious and inclusive religious life. In the context of Nusantara Islam, moderate values ​​are not only manifested in worship practices and social interactions, but are also reflected through art and architecture. The Sheikh Zayed Mosque in Surakarta is a concrete example of cultural acculturation that is full of spiritual and aesthetic meaning. This article aims to examine how batik motifs applied to mosque ornaments reflect messages of religious moderation. With a hermeneutic approach and symbolic analysis, this study examines three main motifs: Lung-lungan, Buket Ukel Tanahan and Kawung—as representations of the values ​​of balance, openness, and tolerance in Islamic teachings. The results of the study show that batik motifs are not merely visual decorations, but also an effective medium of cultural da’wah in strengthening the narrative of Islam rahmatan lil ‘alamin in public spaces. a visual narrative of Islam that is friendly to culture, open to diversity, and strong in principle. These symbols reinforce the message that religious moderation is not only a verbal teaching, but is also embedded in the cultural and aesthetic expressions of Islam Nusantara.